Review of Public Private Partnerships in Irrigation Development in Ghana - Nyamadi, Ben (2018)
AMPPPIDA presentation International Workshop on Assessing Models of Public-Private Partnership for Irrigation Development Mar 13, 2018 - 08:30 am to 02:00 pm GMT